O ativismo judicial e a efetividade do direito fundamental à saúde - Neves, Flávia Soares de Sá (2022)
The discussion about the effectiveness of fundamental rights, in the face of all the inequalities in society, has never lost its relevance. In turn, the issue of the expansion of the Judicial Power has been increasingly highlighted in the media and in academic debates. This dissertation brings reflections on judicial activism, the main object of study, and its consequences for the effectiveness of the fundamental right to health. From a historical overview of the origins of judicial activism, fruit of the growth of society's complexity and the expansion of the Judiciary, we can see the overcoming of positivism and the need for some relativism of the separation of powers theory. Since we are in a country that adopts the Roman-Germanic family system, the research brings to discussion the approximation between the civil law and common law systems, observed nowadays due to the expansion of the Judiciary. It is observed that, as a social right, health claims deal with resources, which are scarce. To carry out the proposed task, the research makes use of a bibliographic literature review, bringing together qualified periodicals, dissertations and theses, legislation, amongst others. Therefore, this study concludes that activist decisions on health, when dealing with the reserve of the possible, should be cautious, demanding the evaluation of the magistrate about the consequences of his decision regarding the allocation of finite resources. The research is justified by the relevance and timeliness of the topics, including judicial activism, health, reserve of the possible, approximation of systems and the separation of powers